Auto-Narratives in Radio Documentary - Bachura-Wojtasik, Joanna; Sygizman, Kinga (Media - Culture - Social Communication, 2019)
This article discusses the issue of the narrative of radio documentary with particular emphasis on auto-narratives in the above-mentioned genre based on the psychological perspective of research on a story. The proposed divisions – fluent versus fragmented auto-narratives and allocentric versus ipsocentric auto-narratives – are illustrated by selected exemplifications. The dialogical nature of the considered artistic genre has a direct impact on this taxonomy.